Soil cover of the military air fields of Ukraine and their possible ecological cleaning (on an example of Pryluky air field) - MENSHOV, O.; SUKHORADA, A.; KRUHLOV, O.; KHOMENKO, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Basic characteristics of the soils of the former military air field of Pryluky and surrounding natural landscapes are considered. Possible ways and prospects of the ecological cleaning of the investigated soils are analysed. The first results of the pedomagnetic investigations are described.